1962
DOI: 10.1002/pol.1962.1205816626
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization by oxidative coupling. IV. Polymerization of 4‐bromo‐ and 4‐chloro‐2,6‐dimethylphenol and preparation and decomposition of the silver and copper salts of certain other phenols

Abstract: In the present paper it has been shown that the 4‐halo‐2,6‐dimethylphenols can be polymerized to high molecular weight poly‐2,6‐dimethylphenylene ethers by the action of cupric ions, providing pyridine is also present. This reaction requires a stoichiometric amount of cupric ions and probably proceeds through complexed phenoxy radicals. Although the polymerization cannot be initiated by catalytic quantities of cupric ions, the same cupric salts which are active in the stoichiometric reaction will initiate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Table 1. MS data for Ni(TBP) 2 (NMIZ) 2 and Cu(TBP) 2 (NMIZ) 2 (The acceptable error limit in data evaluation is ± 2 units).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1. MS data for Ni(TBP) 2 (NMIZ) 2 and Cu(TBP) 2 (NMIZ) 2 (The acceptable error limit in data evaluation is ± 2 units).…”
Section: Resultsmentioning
confidence: 99%
“…A sharp exothermic peak at 116.88 • C and two endothermic peaks at 171.95 • C and 205.83 • C were observed in DSC thermograms of Cu(TBP) 2 (NMIZ) 2 ( Figure 2(a)). Co(TBP) 2 (NMIZ) 2 complexes (Figure 2(b)) showed a sharp exothermic peak at 132.5 • C and an endothermic peak at 184.53 • C ,whereas Ni(TBP) 2 (NMIZ) 2 (Figure 2(c)) showed a single sharp exothermic peak at 143.93 • C. The exothermic peaks are attributed to the new bond formation during polymerization. This vision was previously supported by DSC-IR study (16) which showed the polymer formation at the peak temperature and the increase in the % conversions during polymerization beyond the exothermic peak temperatures.…”
Section: Ni(tbp) 2 (Nmiz)mentioning
confidence: 90%
See 2 more Smart Citations
“…Reactive free radicals on the carbon surface, produced by its oxidation with chlorine, presumably interact with 2,4-dichlorophenol to generate 2,4-dichlorophenoxy radicals by hydrogen abstraction (14). Trichlorodihydroxybiphenyls may be forned by C-C coupling of a 2,4-dichlorophenol molecule and a 2,4-dichlorophenoxy radical, with displacement of a chlorine atom (15). Tetrachloro analogs would be produced if the C-C coupling occurred at unsubstituted ring positions.…”
Section: Resultsmentioning
confidence: 99%